Polymer-Based Delivery of Glucagon-Like Peptide-1 for the Treatment of Diabetes. (30th May 2012) - Kim, Pyung-Hwan; Kim, Sung Wan
Abstract : The incretin hormones, glucagon-like peptide-1 (GLP-1) and its receptor agonist (exendin-4), are well known for glucose homeostasis, insulinotropic effect, and effects on weight loss and food intake. However, due to the rapid degradation of GLP-1 by dipeptidylpeptidase-IV (DPP-IV) enzyme and renal elimination of exendin-4, their clinical applications have been restricted. Although exendin-4 has longer half-life than GLP-1, it still requires frequent injections to maintain efficacy for the treatment of diabetes. In recent decades, various polymeric delivery systems have been developed for the delivery of GLP-1 and exendin-4 genes or peptides for their long-term action and the extra production in ectopic tissues. Herein, we discuss the modification of the expression cassettes and peptides for long-term production and secretion of the native peptides. In addition, the characteristics of nonviral or viral system used for a delivery of a modified GLP-1 or exendin-4 are described. Furthermore, recent efforts to improve the biological half-life of GLP-1 or exendin-4 peptide via chemical conjugation with various smart polymers via chemical conjugation compared with native peptide are discussed.